Indian Supplements to Shakespeare: The Hungry and We That Are Young - Trivedi, Poonam (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
While there is no longer any debate about Shakespeare’s position as a global author, the rapidly expanding worldwide archive of the versioning of his works continues to pose a critical challenge. Questions like how far and to what extent can this be seen as Shakespeare or not Shakespeare are raised. Estimation of value is vexed, too: does it reside mainly in the local, or can it also extrapolate meaning globally? Methodologies, too, are debated: is archiving the starting or the endpoint of reception? Or is the construction of networks of analyses around and between them the mode towards negotiating appreciation? Taking a leaf out of Derrida’s “That Dangerous Supplement,” this paper will propose a critical perspective of supplementarity as an intervention in the debate on the proliferating versioning of Shakespeare. This sees the traffic in Shakespeare as both a surplus, a plenitude enriching another plenitude and also a substitute filling a void. It considers translation, adaptation, appropriation, and even performance of Shakespeare as additions which enhance and complete making good an insufficiency. It will locate this discussion on two much-acclaimed adaptations to emerge out of India: the film The Hungry (2017), directed by Bornila Chatterjee, of Titus Andronicus, and the novel We That Are Young (2017) by Preti Taneja, based on King Lear.